2003
DOI: 10.3201/eid0905.020428
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Incidence of Typhoid Fever and Other Febrile Illnesses in Developing Countries

Abstract: To measure the incidence of typhoid fever and other febrile illnesses in Bilbeis District, Egypt, we conducted a household survey to determine patterns of health seeking among persons with fever. Then we established surveillance for 4 months among a representative sample of health providers who saw febrile patients. Health providers collected epidemiologic information and blood (for culture and serologic testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
170
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(172 citation statements)
references
References 17 publications
1
170
0
1
Order By: Relevance
“…The emergence of new quinolone resistance pattern in Salmonella enterica which are susceptible to NA but exhibit reduced susceptibility to ciprofloxacin was also reported from South Asia. 8 S. Typhi and S. Paratyphi A with reduced susceptibility to fluoroquinolones and resistance to nalidixic acid require higher MICs of ciprofloxacin and other fluoroquinolones, 9 although they are still considered susceptible according to current CLSI interpretive criteria. In our study, the 2 isolates of S. Typhi which were susceptible to ciprofloxacin in disc diffusion test showed reduced susceptibility to ciprofloxacin in the MIC test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of new quinolone resistance pattern in Salmonella enterica which are susceptible to NA but exhibit reduced susceptibility to ciprofloxacin was also reported from South Asia. 8 S. Typhi and S. Paratyphi A with reduced susceptibility to fluoroquinolones and resistance to nalidixic acid require higher MICs of ciprofloxacin and other fluoroquinolones, 9 although they are still considered susceptible according to current CLSI interpretive criteria. In our study, the 2 isolates of S. Typhi which were susceptible to ciprofloxacin in disc diffusion test showed reduced susceptibility to ciprofloxacin in the MIC test.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although fluoroquinolones, if susceptible, clinicians should be aware of the possibility of the treatment failures of infections with S. Typhi and S. Paratyphi A strains. 9 So, it is important to monitor the increases in the MIC of fluoroquinolones in S. Typhi and emerging strains of S. Paratyphi A. 17 Therefore, the present study was undertaken to evaluate the antibiotic susceptibility pattern of isolated Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of investigators [27] [32] and recent data gives an estimate of 8 cases per 100,000 [21,22].…”
Section: Tunisiamentioning
confidence: 99%
“…17 A more recent study by Crump et al, however, reported lower IR of 13/100,000 persons. 16 Most cases in developed countries arise in travellers and domestically acquired disease is very rare.…”
Section: Epidemiologymentioning
confidence: 99%